Cibermetría del Web: Las leyes de exponenciación. - Alonso Berrocal, José Luis (Revista General de Información y Documentación, 2001)
An introduction to the power laws, enunciated by Michalis Faloutsos, is made and tbat allows us tu make a characterization of the Web through the analysis of their topology. Their most important characteristics are described and how calculate some of ihe values of thc most interesting functions.